Climate, duration, and N placement determine N2O emissions in reduced tillage systems: a meta‐analysis. (3rd August 2012) - van Kessel, Chris; Venterea, Rodney; Six, Johan; Adviento‐Borbe, Maria Arlene; Linquist, Bruce; van Groenigen, Kees Jan
Abstract: No‐tillage and reduced tillage (NT/RT) management practices are being promoted in agroecosystems to reduce erosion, sequester additional soil C and reduce production costs. The impact of NT/RT on N2 O emissions, however, has been variable with both increases and decreases in emissions reported. Herein, we quantitatively synthesize studies on the short‐ and long‐term impact of NT/RT on N2 O emissions in humid and dry climatic zones with emissions expressed on both an area‐ and crop yield‐scaled basis. A meta‐analysis was conducted on 239 direct comparisons between conventional tillage (CT) and NT/RT. In contrast to earlier studies, averaged across all comparisons, NT/RT did not alter N2 O emissions compared with CT. However, NT/RT significantly reduced N2 O emissions in experiments >10 years, especially in dry climates. No significant correlation was found between soil texture and the effect of NT/RT on N2 O emissions. When fertilizer‐N was placed at ≥5 cm depth, NT/RT significantly reduced area‐scaled N2 O emissions, in particular under humid climatic conditions. Compared to CT under dry climatic conditions, yield‐scaled N2 O increased significantly (57%) when NT/RT was implemented <10 years, but decreased significantly (27%) after ≥10 years of NT/RT. There was a significant decrease in yield‐scaled N2 O emissions in humid climates when fertilizer‐N was placed at ≥5 cm depth. Therefore, in humid climates, deep placement of fertilizer‐N is recommended when implementing NT/RT. In addition, NT/RT practices need to be sustained for a prolonged time, particularly in dry climates, to become an effective mitigation strategy for reducing N2 O emissions.